Comparison of caspofungin MICs by means of EUCAST method EDef 7.1 using two different concentrations of glucose - Rodriguez-Tudela, Juan Luis (2010)
According to the product insert for Cancidas (caspofungin acetate), the drug must not be diluted in solutions containing glucose as this decreases caspofungin stability. The aim of this study was to compare caspofungin MICs for a collection of yeasts by means of EUCAST method EDef7.1 but using two different concentrations of glucose: 2% versus 0.2%. MICs were identical or within one 2-fold dilution for 93 out of 95 strains (97.9%), showing that glucose does not interfere with susceptibility.